50 studies every global health provider should know - Walker, Andrea (Andrea D.); Agarwal, Anup, MBBS; Jain, Yogesh (New York, NY : Oxford University Press, 2023)
Global health is a broad field that is fundamentally about healthcare equity and health as a human right, whether in high- or low-income countries, rural areas, or inner cities. Although understanding disease processes and treatments is important to providing health care, of equal importance is an understanding that the conditions in which people live and work affect a wide range of health outcomes.'50 Studies Every Global Health Provider Should Know' presents a diverse series of studies that illustrate key issues to consider in achieving health care as a human right.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on August 30, 2023).
Keywords: World health; Medical care; Social medicine; Diseases; Surgery; Mental health; Children -- Health and hygiene; Women -- Health and hygiene; Health and Wellbeing; Social services & welfare, criminology